Studi Kasus Putusan Pengadilan Niaga Nomor 04/Pdt.Sus-Pailit/2023 PN Niaga Mdn jo. Pengadilan Niaga Nomor 18/Pdt.Sus-Renvoi/2023/PN Niaga Mdn Terkait Penerapan Asas Erga Omnes dan Asas Promulgatie Ditinjau dari Undang-Undang Nomor 37 Tahun 2004 tentang Ke - Assyura Zumarnis (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Receivable disputes may be resolved through bankruptcy mechanisms that culminate in a bankruptcy ruling. However, legal issues may still arise post-verdict, such as in Commercial Court Decision Number 18/Pdt.Sus-Renvoi/2023/PN Niaga Mdn, where the receivable claim filed by the Ministry of Environment and Forestry was rejected due to late submission. In resolving the case, the judge considered two legal principles: erga omnes and promulgatie. This paper aims to examine the position of these principles in bankruptcy cases and analyze the judge’s legal reasoning regarding the late submission of receivables under Indonesian bankruptcy law. This study uses a normative juridical approach, with the research specification being analytical-descriptive in nature. The data are secondary in form and are collected through literature review. The method of data analysis employed is qualitative normative analysis. The findings of this study show that the erga omnes and promulgatie principles hold a significant position within Indonesian bankruptcy law. These principles are implicitly reflected in Article 15 paragraph (4) and Article 24 paragraph (1) of the Bankruptcy Law (UUKPKPU). These principles apply insofar as there are no specific provisions limiting their application. In this case, the judge's legal reasoning in deciding the renvoi procedure is deemed inaccurate because there is a specific provision that governs the late submission of receivable claims. Therefore, the application of the erga omnes and promulgatie principles should have been subject to such limitation.